Combining fusion-based and solid-state additive manufacturing: Investigation of additive DED structures with friction surfacing interlayer - Kallien, Zina; Eimer, Eloise; Roos, Arne; Ortolland, Victor; Rath, Lars; Williams, Stewart; Klusemann, Benjamin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Fusion-based additive manufacturing (AM) techniques face some challenges for aluminium due to the necessity of material melting resulting in insufficient bonding. The present work provides a novel insight into the combination of fusion-based and solid-state AM approaches to successfully generate structures from different aluminium alloys. Specifically, the friction-based solid-state AM technique of friction surfacing (FS) is used to generate an interlayer structure on AA2050 substrate material. On top of this structure, additional AA5087 is deposited via Wire and Arc Additive Manufacturing (WAAM). For the FS interlayer structure, two different alloys, AA5083 and AA7050, are explored. Additionally, the effect of inter-layer rolling is investigated for the final WAAM structure. The built structures are investigated with special focus on the interfaces, i.e., FS deposit-to-substrate and WAAM deposit-to-FS deposit interfaces. In the cross sections, no defects could be detected at the FS deposit-to-substrate interfaces and the structures did not show visible cracks at the WAAM deposit-to-FS deposit interfaces. The investigation showed that the mechanical properties of the WAAM structure improve when inter-layer rolling is applied, leading to homogeneous mechanical properties across the interfaces. The study highlights that FS as friction-based solid-state AM process is capable to build interlayer structures for material combinations, which cannot be achieved directly via a fusion-based process. The approach of combining different AM techniques can be advantageous not only to achieve a dissimilar material combinations but also to build hybrid structures with locally optimized properties.
Keywords: Wire and Arc Additive Manufacturing (WAAM); Friction Surfacing; Dissimilar Aluminium Alloy; Interface; Micro-flat Tensile Testing